Molecular Characterization and Antibiotic Resistance Patterns of Listeria Species in Frozen Beef and Chicken Sold in Benin City, Nigeria - Omogbai, Barry Aigbodion; Esokpunwu, David Eguasa (Food and Applied Bioscience Journal, 2018)
Frozen beef and chicken products were purchased from four markets in Benin City and examined for the presence of Listeria species using standard microbiological procedures. Listeria species were characterized by biochemical tests and confirmed by polymerase chain reaction (PCR). Antibiotic resistance of the isolates was carried out using the disc diffusion method. Bacterial plasmids were isolated and separated by agarose gel electrophoresis. The Listeria isolates in the beef samples ranged between 3.11 ± 0.69 × 103 to 1.36 ± 0.39 × 104 CFU/g while for chicken samples ranged between 1.56 ± 0.24 × 103 to 1.84 ± 0.45 × 104 CFU/g. The isolated Listeria species were L. monocytogenes, L. ivanovii, L. grayi and L. innocua. Among the Listeria isolates, L. monocytogenes (34.78%) and L. innocua (31.82%) had the highest frequency in beef and chicken respectively. Antibiotics sensitivity revealed that the most resisted drugs were ampiclox, amoxicillin and septrin while isolates were most susceptible to gentamycin and ciprofloxacin. The strains of organisms identified from DNA sequencing were: L. monocytogenes (KM010020.1), L. monocytogenes (KF588563.1), L. ivanovii subsp. Ivanovii (CP009577.1), L. grayi (JN852815.1), L. monocytogenes (CP013724.1), L. ivanovii subsp. londoniensis (CP009575.1), L. grayi (NR116351.1) and L. innocua (KU208087.1). The food-borne pathogens isolated from meat products of this study may be the indicator of poor hygienic practices.